Unemployment Insurance Generosity and Aggregate Employment - Christopher Boone; Arindrajit Dube; Lucas Goodman; Ethan Kaplan (Institute of Labor Economics (IZA), 2016)
This paper examines the impact of unemployment insurance (UI) on aggregate employment by exploiting cross-state variation in the maximum benefit duration during the Great Recession. Comparing adjacent counties located in neighboring states, we find no statistically significant impact of increasing UI generosity on aggregate employment. Our point estimates are uniformly small in magnitude, and the most precise estimates rule out employment-to-population ratio reductions in excess of 0.32 percentage points from the UI extension. We show that a moderately sized fiscal multiplier can rationalize our findings with the small negative labor supply impact of UI typically found in the literature.
Keywords: J65; E62; E32; 330; labor supply; unemployment insurance; fiscal multiplier